Teachers' Challenges in Implementing Vocabulary Games in English Class for the Tenth Grade of - Amalia, Rezki; Latief, Hasnawati; Yulianti Natsir, Ratu (FKIP Unismuh Makassar, 2023)
This research aims to determine the challenges faced by teachers in implementing vocabulary games in the tenth grade at SMAN 7 Selayar. This study uses a qualitative descriptive method conducted with an English teacher at SMAN 7 Selayar to find out the challenges faced by teachers in implementing vocabulary games in classroom learning. This study uses checklist observations and interviews as instruments in data collection.The results of this research indicate that there are two factors that become a challenge for teachers in learning English in vocabulary games applied at SMAN 7 Selayar, namely internal and external factors, in which internal factors come from the teacher himself while external factors come from students. The teacher's internal challenges are the limited vocabulary of students and lazy students, while the external challenges of teachers are creative learning/teachers, and also limited learning time when using games.